Contingent, temporary unemployment insuranceàs impacts on employment and unemployment durations - Kailing Shen (Institute for the Study of Labor (IZA), 2007)
This paper studies contingent, temporary unemployment insurance (UI) coverage's impacts on employment and unemployment durations using a duration model extended with heaping considerations and a recent Canadian panel data. A unique source of identification here is the Employment Insurance (EI) reform of Canada in the 1996. Based on the estimated coefficients from the duration models, the simulations suggest that UI increases unemployment rates by 2% and 5% in the non-seasonal and seasonal sectors respectively.
Keywords: 330